2010
DOI: 10.1002/chem.200901623
|View full text |Cite
|
Sign up to set email alerts
|

From Salts to Ionic Liquids by Systematic Structural Modifications: A Rational Approach Towards the Efficient Modular Synthesis of Enantiopure Imidazolium Salts

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 98 publications
(39 reference statements)
0
21
0
Order By: Relevance
“…In the ATR‐FTIR spectra of 7a – 12a , the bands between 3150 and 3000 cm –1 are considered diagnostic of the C–H stretching modes of the aromatic rings 6b,15. In this region, for the imidazolium aromatic ring, the vibrational bands at higher wavenumbers correspond to C6–H and C7–H stretching modes, whereas vibrational bands at lower wavenumbers correspond to the C5–H stretching mode.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the ATR‐FTIR spectra of 7a – 12a , the bands between 3150 and 3000 cm –1 are considered diagnostic of the C–H stretching modes of the aromatic rings 6b,15. In this region, for the imidazolium aromatic ring, the vibrational bands at higher wavenumbers correspond to C6–H and C7–H stretching modes, whereas vibrational bands at lower wavenumbers correspond to the C5–H stretching mode.…”
Section: Resultsmentioning
confidence: 99%
“…CILs have additional potential as chiral solvents,12 shift reagents,13 or enantioselective catalysts 14. Furthermore, it has recently been shown that the configuration of the resulting CILs plays an important role in defining their final physical properties 15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Our study has shown that the use of racemic mixtures can be a useful strategy to lower the melting point of an ionic liquid while maintaining its chemical composition. 25 In fact, in several chiral imidazolium salts, the racemic salts have higher melting points than the enantiopure salts.…”
Section: Correlation Between Chirality and Melting Pointsmentioning
confidence: 99%
“…Studies on metal-containing ionic liquids 4 and protonic ionic liquids 5 with branched alkyl substituents revealed that these compounds tend to exhibit lower glass-transition temperatures and remain in the liquid state due to suppression of crystallization. 25 Chirality is an important issue in molecular compounds. However, while branched substituents often have chiral centers, relatively few studies have focused on how chirality affects the thermal properties of ionic-liquid-related materials.…”
Section: Introductionmentioning
confidence: 99%